Down-regulation of LINC-ROR, HOXA-AS2 and MEG3 in gastric cancer. Issue 10 (October 2022) - Soghala, Shahrad; Harsiny, Kiana; Momeni, Parto; Hatami, Mahsa; Kholghi Oskooei, Vahid; Hussen, Bashdar Mahmud; Taheri, Mohammad; Ghafouri-Fard, Soudeh
Abstract: Long non-coding RNAs (lncRNAs) have been identified as modulators of gastric carcinogenesis. Evaluation of expression amounts of these transcripts is a primary but essential step for recognition of the role of lncRNAs in the carcinogenesis. Therefore, we compared expressions of LINC-ROR, HOXA-AS2, MEG3 and HOTTIP lncRNAs in gastric cancer samples and nearby non-cancerous samples. Expression levels of LINC-ROR, HOXA-AS2 and MEG3 lncRNAs have been lower in gastric cancer samples compared with nearby non-cancerous samples (Expression ratios = 0.26, 0.37 and 0.36; P values = 0.021, 0.015 and 0.032, respectively). However, expression levels of HOTTIP were not significantly different between gastric cancer tissues and nearby tissues (P value = 0.43). HOTTIP expression was associated with tumor size (P value = 0.04). In addition, MEG3 expression was associated with site of primary tumor (P = 0.0003). Expressions of LINC-ROR and HOXA-AS2 were not associated with any clinical or pathological parameter. ROC curve analysis revealed that HOXA-AS2 and LINC-ROR could significantly differentiate between gastric cancer samples and nearby non-cancerous tissues (AUC values = 0.68 and 0.64; P values = 0.01 and 0.04, respectively). Taken together, the current investigation provides clues for contribution of LINC-ROR, HOXA-AS2 and MEG3 lncRNAs in gastric carcinogenesis and warrants further mechanistical assays. Abstract : Gastric cancer; LINC-ROR ; HOXA-AS2 ; MEG3 ; HOTTIP ; lncRNA.